Interpersonal Communication in Professional and Social Meetings: Exploring Best Practices for Meaningful Human Encounters - Chowdhary, Ruchita Sujai; Arun Kumar Sinha (UIR Press, 2026)
Interpersonal communication plays a vital role in determining the effectiveness and outcomes of professional and social meetings. Although meetings are a routine part of academic, organizational, and community life, many fail to produce meaningful interaction or productive dialogue. These shortcomings often stem from poor communication practices, rigid hierarchies, unequal participation, and limited empathetic engagement. In the contemporary era of digital distractions and time constraints, the human dimension of meetings is frequently overlooked, negatively affecting collaboration and decision-making. This study examines best practices of interpersonal communication that promote meaningful human encounters in meeting contexts. A qualitative research design was employed, utilizing in-depth interviews, focus group discussions, and systematic observations across various professional and social settings. The analysis focuses on verbal exchanges, listening behaviors, non-verbal communication, emotional intelligence, and relational dynamics among participants. Special attention is given to the influence of power relations and communication styles on participation and mutual understanding. The findings indicate that active listening, empathetic responsiveness, respectful communication, and inclusive participation significantly improve trust, cooperation, and collective problem-solving. In contrast, barriers such as dominance by authority figures, inattentiveness, digital multitasking, and dismissive behaviors hinder effective interpersonal engagement. The study highlights the importance of human-centered communication ethics, reflective interaction practices, and emotional awareness in creating more productive meeting cultures. By providing practical recommendations, this research contributes to the understanding of interpersonal communication in organizational and social environments. It offers actionable insights for educators, administrators, professionals, and community leaders seeking to enhance the quality of interaction and relational outcomes in meetings. Strengthening interpersonal communication practices is essential for fostering collaboration, mutual respect, and more meaningful human encounters in both formal and informal meeting contexts.